Menentukan harga jual warung makan Sunda Chicken berdasarkan metode full cost pricing - Dojeng Meisi Koo; Agus Munandar (Entrepreneurship Bisnis Manajemen Akuntansi (E-BISMA), 2022)
This study aims to help analyze the selling price at the Sunda Chicken food stall. In accordance with interviews conducted by the author, the Sunda Chicken food stall suffered losses due to the instability of raw material prices. This is because the Sunda Chicken food stall does not set a selling price based on production costs, but is adjusted based on market prices and consumer desires. Therefore, the author uses the full cost pricing method to calculate the new selling price as a form of solution offered to the Sunda Chicken food stall. Full cost pricing is one of determining selling price methods based on production costs and the percentage of expected profit. The author uses qualitative methods in the preparation of research journals, namely doing calculations based on data obtained from the owner of the food stall. The results of the research show that there is a difference in the selling price between the initial price of the Sunda Chicken food stall and the new price after calculating the full cost pricing method.